Integrating Islamic Ethics Into Pro-Environmental Behaviour: A Systematic Literature Review And Proposed Conceptual Framework - Eko Susanto; Siti Hafsah Zulkarnain (Journal of Consumer Studies and Applied Marketing, 2026)
The integration of Islamic ethics into pro-environmental consumer behavior has emerged as a rapidly expanding research domain; however, extant frameworks remain fragmented. This study aims to synthesize global literature on green consumption within an Islamic context through a Systematic Literature Review (SLR). Utilizing the PRISMA 2020 protocol, 78 Scopus-indexed articles published between 2015 and 2025 were analyzed to identify theoretical antecedents and behavioral barriers. The findings propose the Integrated Islamic Green Behavior Model (IIGBM), which incorporates three primary structural pathways: the Stewardship Pathway (Khalifah), the Balance Pathway (Mizan), and the Wholesomeness Pathway (Thayyib). The analysis reveals a significant "green gap," in which high spiritual intentions are frequently constrained by moderating factors such as premium pricing, limited product availability, and institutional policy constraints. This study concludes that transitioning from a "Halal" compliance orientation toward "Thayyib" ethical values is a critical strategy for converting transcendental accountability into tangible market actions. The theoretical contribution of this research adds a novel dimension to Norm Activation Theory by incorporating a divine ethical calculus into the discourse of sustainable consumerism. The findings further demonstrate that Islamic ethical principles provide explanatory mechanisms beyond conventional environmental behavior theories by embedding divine accountability into sustainable consumption decisions. The theoretical contribution of this research extends the Theory of Planned Behavior (TPB), the Value-Belief-Norm (VBN) theory, and the Norm Activation Theory (NAT) by integrating Khalifah (stewardship), Mizan (balance), and Thayyib (wholesomeness) as distinct pathways linking spiritual responsibility to pro-environmental behavior.